Investigation of cutting temperature in minimum quantity lubrication milling of ferritic stainless steel by using multi wall carbon nanotube reinforced cutting fluid - Uysal, Alper (GAZI UNIV, FAC ENGINEERING ARCHITECTURE, 2017)
Stainless steel materials have been used in many areas such as automotive, food, medical, chemical etc. by performing machining operations although having low thermal conductivity and work hardening tendency during machining. Cutting fluids have been applied in the machining of these materials. However, the cutting fluids have disadvantages such as harmful to the environment and health and the cost increment due to plenty of usage. Therefore, in this study, MWCNT (Multi-Walled Carbon Nanotube) reinforced commercial vegetable cutting fluid and WC (Tungsten Carbide) cutting tool were used in the milling of ferritic stainless steel by MQL (Minimum Quantity Lubrication) method. MWCNT particles were added to the cutting fluid at ratios of 0.1% wt., 0.15% wt. and 0.2% wt. to improve its cooling and lubricating properties. The effects of MWCNT particles, mixture ratios, and MQL flow rate on the cutting temperature occurred during milling operation were determined. The addition of MWCNT to the cutting fluid caused a decrement on the cutting temperature. However, an increment was observed when mixture ratio was further increased. Additionally, increasing of MQL flow rate reduced the cutting temperature.
Keywords: Minimum quantity lubrication; milling; cutting temperature; multi-walled carbon nanotube; ferritic stainless steel; SURFACE-ROUGHNESS; TOOL WEAR; OPTIMIZATION; FAILURE; Engineering